Analytical process model for wire plus arc additive manufacturing - Rios Contesse, Sergio Eduardo; Colegrove, Paul A.; Martina, Filomeno; Williams, Stewart W. (My University, 2018)
An analytical process model for predicting the layer height and wall width from the process parameters was developed for wire + arc additive manufacture of Ti-6Al-4V, which includes inter-pass temperature and material properties. Capillarity theory predicted that cylindrical deposits were produced where the wall width was less than 12 mm (radius < 6 mm) due to the large value of the surface tension. Power was predicted with an accuracy of +/- 20% for a wide range of conditions for pulsed TIG and plasma deposition. Interesting differences in the power requirements were observed where a surface depression was produced with the plasma process due to differences in melting efficiency and/or convection effects. Finally, it was estimated the impact of controlling the workpiece temperature on the accuracy of the deposit geometry.
Keywords: wire plus arc additive manufacture; welding capillarity; point source conduction